KEMUNGKINAN PEMILIHAN METODE NILAI WAJAR BAGI PERUSAHAAN YANG MELAPORKAN PROPERTI INVESTASI - Sri Putri Siska Mulyanti; Yeasy Damayanti; Yunilma Yunilma (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2020)
This study aims to examine the factors that affect the likelihood companies choose the method of fair value for investment properties. Factors in this research consisted of debt levels, the size of the company, information asymmetry and companies in the property industry (control variables). The population of this research is company publicly traded listed on the Indonesian Stock Exchange 2010-2015 period. The sample selection using purposive sampling, the type of data used is secondary data obtained from the official website of the Stock Exchange. The hypothesis tested using a binomial logit regression models. The results of this study indicate that the level of debt significantly influence the possibility of the selection method for the fair value of investment property. This suggests that the high or low levels of debt may affect the selection of the fair value method. The size of the company, information asymmetry and companies in the property industry did not significantly affect the possibility of the selection method for the fair value of investment property. This suggests that the high or low of company size, and information asymmetry in the property industry has no impact on the possibility of the selection method for the fair value of investment property